Self-powered Sensors and Systems Based on Nanogenerators - Zhiyi Wu (Sensors, 2020)
Sensor networks are essential for the development of the Internet of Things and the smart city. A general sensor, especially a mobile sensor, has to be driven by a power unit. When considering the high mobility, wide distribution and wireless operation of the sensors, their sustainable operation remains a critical challenge owing to the limited lifetime of an energy storage unit. In 2006, Wang proposed the concept of self-powered sensors/system, which harvests ambient energy to continuously drive a sensor without the use of an external power source. Based on the piezoelectric nanogenerator (PENG) and triboelectric nanogenerator (TENG), extensive studies have focused on self-powered sensors. TENG and PENG, as effective mechanical-to-electricity energy conversion technologies, have been used not only as power sources but also as active sensing devices in many application fields, including physical sensors, wearable devices, biomedical and health care, human–machine interface, chemical and environmental monitoring, smart traffic, smart cities, robotics, and fiber and fabric sensors. In this review, we systematically summarize the progress made by TENG and PENG in those application fields. A perspective will be given about the future of self-powered sensors.